SCREENING FOR HYPERCHOLESTEROLEMIA IN 5 YEAR OLD CHILDREN IN SLOVENIA - Nataša Uršič-Bratina; Nada Saje-Hribar; Nina Bratanič; Mojca Žerjav-Tanšek; Vojko Berce; Ciril Kržišnik; Tadej Battelino, za Stalno strokovno skupino za predšolsko medicino (Zdravniški Vestnik, 2003)
Background. Cardiovascular diseases represent the most frequent cause of morbidity and mortality in developed countries. Blood cholesterol concentration influences the progression of atherosclerosis and most developed countries started programs for early detection of hypercholesterolemia. The study presents data analysis related to the total cholesterol concentrations obtained from 5-year old children. Additionally, guidelines for improving the follow-up work with children having hypercholesterolemia are presented. Methods. Values of total cholesterol concentration of 2742 children born 1995 or 1996 were obtained from 17 pediatric primary care facilities in Slovenia. Data analysis included values of body mass index (BMI). The study was approved by the State Committee for Medical Ethics (103/02/02). Results. Values of total cholesterol concentration were not distributed according to the normal distribution. Total cholesterol concentration was significantly higher in girls (median 4.41 mmol/L, 5th percentile 3.3 mmol/l and 95th percentile 5.8 mmol/L) compared to boys (median 4.3 mmol/L, 5th percentile 3.2 mmol/l and 95th percentile 5.6 mmol/L) (p < 0.0001). Twenty-one percent of values were above 5 mmol/L, 15% above 5.2 mmol/L and 2.8% above 6 mmol/L. Total cholesterol concentration did not correlate with the BMI. Conclusions. The results of the present study are in accordance with other similar published studies. General screening for hypercholesterolemia in childhood is feasible and medically indicated. Twenty-one percent of Slovenia population has total cholesterol concentration above 5 mmol/L. The follow-up work with these children must be structured and well planned. The main advantage of early detection of hypercholesterolemia is in the possibility of starting the changes of eating habits and life-style early in childhood. Namely, these changes are easier to perform and more successful if started early.